Multilevel determinants of antiretroviral therapy initiation and retention in the test-and-treat era of Nepal: a qualitative study - Archana Shrestha; Lisasha Poudel; Soniya Shrestha; Niharika Jha; Bihari Sharan Kuikel; Prakash Shakya; Rajya Shree Kunwar; Lok Raj Pandey; Man Bahadur KC; Erin C. Wilson; Keshab Deuba (BMC, 2024)
Abstract Background The transition to the "test-and-treat" policy in Nepal in 2017, coupled with the rapid initiation of antiretroviral therapy (ART) in 2020, necessitates an in-depth understanding of factors influencing ART initiation and retention. This study investigates these factors from the perspectives of healthcare providers, families/communities, and people living with HIV (PLHIV). Methods Employing a qualitative design, in-depth interviews were conducted with 24 ART clients and 26 healthcare providers across different provinces of Nepal. A comprehensive interview guide facilitated the exploration of experiences and perceptions. Interviews were transcribed verbatim, and thematic analysis was applied to distill key insights. Guided by a socio-ecological model, interviews were analyzed to identify the barriers and facilitators to ART initiation and continuation at the individual, family/community, and health system levels. Results Facilitators and barriers were identified at three levels. Individual-level facilitators included fear of death, perceived health benefits, knowledge about HIV/ART, confidentiality, and financial support. Barriers encompassed concerns about lifelong medication, side effects, denial of HIV status, fear of disclosure, and financial constraints. At the family/community level, support from family and community health workers facilitated ART adherence, while social stigma and discrimination posed barriers. The health system's role was dual; the provision of free treatment, a client tracking system and a robust drug supply chain were facilitators, whereas logistical challenges and service accessibility during the COVID-19 pandemic were notable barriers. Conclusions This study highlights the various factors that influence ART initiation and retention in Nepal during the test-and-treat era. Tailored interventions should focus on increasing awareness about HIV and ART, strengthening healthcare systems, ensuring availability of medications, and providing accessible treatment during service disruptions. Furthermore, these interventions should encourage supportive environments at the individual, community, and healthcare system levels. Taking this holistic approach is essential for effectively implementing ART and achieving long-term health outcomes in light of changing public health policies.